Analisis Jumlah Penduduk, Produk Domestik Regional Bruto (PDRB) dan Belanja Daerah terhadap Pendapatan Asli Daerah (PAD) di Kabupaten Pacitan - Charrel Ferdiansyah; Syamsul Huda (Journal of Management and Bussines (JOMB), 2024)
This research aims to evaluate the influence of population, gross regional domestic product (GRDP), and regional expenditure on PAD from 2012 to 2021. The results of the study show that partially, population and regional expenditure have a positive but not significant influence on PAD, while GRDP has a positive and significant influence on PAD. Simultaneously, these three variables have a significant influence on PAD in Pacitan Regency. In conclusion, the importance of effective local economic management in increasing PAD and community welfare in the area. Keywords: Regional Expenditure, Population, Gross Regional Domestic Product, Regional Original Income